Implementation of a Smoking Cessation Education Program in the Emergency Department. (July 2018) - González, Juan M.; de Tantillo, Lila; Snowden, Kenya; Gattamorta, Karina; Ortega, Johis
Abstract : Tobacco use is a major threat to public health. Current guidelines suggest that healthcare professionals in the emergency department provide routine smoking cessation screening and interventions. Evidence suggests that an educational intervention among registered nurses in the emergency department may increase education and referral for smoking cessation of patients who use tobacco products. An educational module regarding smoking cessation counseling was provided to registered nurses in the emergency department at a private hospital in South Florida. A pre- and postintervention self-reported survey evaluated changes in nurses asking about tobacco use; advising to quit; assessing readiness, assisting, and arranging follow-up for patients who smoke to quit; and encouraging pharmacological agents. All participating nurses screened for tobacco use most of the time before and after the intervention. However, the number of nurses who assessed readiness, assisted, arranged follow-up for patients and encouraged the use of pharmacological agents increased significantly in the postsurvey. Study findings agree with previous research indicating that nurses routinely screen for tobacco and advise to quit. However, implementing smoking cessation education and referral resources may better equip registered nurses in the emergency department to take an active role initiating follow-up interventions for patients who screen positive for tobacco use. Educational interventions among these nurses can increase knowledge of and utilization of existing resources to help patients quit.